Appl.Math. 2017
DOI: 10.21136/am.2017.0182-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of continuous distributions through inequalities involving the expected values of selected functions

Abstract: Characterizations of continuous distributions through inequalities involving the expected values of selected functions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Hence, by taking X t as reference, with g(x) = − log f (x) and integrating by parts, similarly as Eq. (3.9) of Goodarzi et al [18], we obtain (34).…”
Section: Some Applicationsmentioning
confidence: 52%
See 2 more Smart Citations
“…Hence, by taking X t as reference, with g(x) = − log f (x) and integrating by parts, similarly as Eq. (3.9) of Goodarzi et al [18], we obtain (34).…”
Section: Some Applicationsmentioning
confidence: 52%
“…Furthermore, a sharp uniform bound on varentropy for log-concave distributions is found in the work of Madiman [28]. An alternative way to calculate a bound for varentropy is discussed in Goodarzi et al [18] where the authors use some concepts of reliability theory. The generalization from log-concave to convex measures has been studied in the work of Li et al [26] where a bound on the varentropy for convex measures is discussed.…”
Section: Varentropymentioning
confidence: 99%
See 1 more Smart Citation
“…They had shown that Var[− ln f (X)] 2 9 , whereas by using (2.20), we can obtain lower bound 0.103985 for varentropy. The new lower bound is not sharper than the lower bound [12], however its calculation is very straightforward.…”
Section: Resultsmentioning
confidence: 92%
“…Let X have beta distribution with parameters a = 2 and b = 1. Goodarzi et al [12] obtained a lower bound for the varentropy of random variable X. They had shown that Var[− ln f (X)] 2 9 , whereas by using (2.20), we can obtain lower bound 0.103985 for varentropy.…”
Section: Resultsmentioning
confidence: 96%